Innovative methods of using laser scanning and geoinformation systems for design of communication routes - Panchenko, Sergii; Ugnenko, Yevgeniia; Yurchenko, Valentina; Uzhviieva, Elena; Korostelov, Yevhen; Sorochuk, Nataliia (International Conference “Environmental Engineering”, 2023)
The article substantiates the use of laser scanning and Geoinformation systems (GIS) for the design of connection roads repairs. Choosing a particular way to organize data in GIS is key. The choice of data model directly determines many of the functionality of the GIS being created. The organization of data in GIS directly determines the applicability of certain technologies of data entry. To the same extent, it affects the achievable spatial accuracy of presenting the graphic part of information, the ability to obtain high-quality cartographic material, and the organization of map quality control. To a large extent, the way data is organized in GIS also determines the achievable performance of the system, for example, when executing a query or visualizing it on the screen. The ability to work with large amounts of data or with accurate data over large areas is also related to the ways and forms of data organization. The convenience of editing and updating data, the ability of an organization designed to work in multi - user editing mode, and the creation of databases distributed over a network - all this is also primarily related to the organization of data, and secondly to specific software.
Keywords: geoinformation systems (GIS); laser scanning; design of communication routes; connection roads repairs; innovative methods